International activity of sports universities: state and trends of development - Lubysheva, L. I.; Rosenko, S. I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify current trends and determine the vector of development of the international activities of Russian universities of physical culture and sports.